Osteochondroma of the First Phalanx in Tbourida Horses - Seghrouchni, Mohammed; Bollo, Enrico; Piro, Mohamed; Alyakine, Hassan; Bouayad, Hassan; Chakir, Jamal; Azrib, Rahma; Allali, Khalid El (Frontiers in Veterinary Science, 2019)
The present study aimed to describe the anatomo-histopathological and the imaging features using computed tomography and magnetic resonance imaging on six ex vivo forelimbs of Tbourida horses presenting a particular bone exostosis on the dorsal and proximal part of the first phalanx diagnosed by X-ray. Gross anatomy of the bone exostosis revealed an irregular surface with poly-lobulated tissue masses showing a cauliflower shape. The diameter/depth varied from 0.5 to 5.1 cm with a mean of 3.9±0.9 cm. The capsule of the metacarpophalangeal joint was hypertrophic and showed many invaginations in the inner part, in contact with the bone exostosis. Computed tomography revealed cortical and medullary continuity of the bone exostosis with the underlying bone, and remodeling of the cortical surface of the dorsal and proximal part of the first phalanx. Magnetic resonance imaging showed an increased signal intensity of the bone exostosis on T1 and T2* weighted gradient echo fast. Histological examination of the bone exostosis revealed a cap of hyaline cartilage, including large foci of endochondral ossification with a base of cancellous bone surrounding marrow spaces, which confirmed the diagnosis of osteochondroma. The capsule of the metacarpophalangeal joint showed a large amount of recently formed connective tissue fibers in its inner part interspersed with mature connective tissue. The hyperextension of the metacarpophalangeal joint during the Tbourida show on a hard ground surface, and the use of hobbles during horse stabling are probably responsible for the outgrowth of osteochondroma with different shape and size, and fracture complication in some cases.